2022
DOI: 10.15549/jeecar.v9i5.1063
|View full text |Cite
|
Sign up to set email alerts
|

Capital structure, profitability, hedging policy, firm size, and firm value: Mediation and moderation analysis

Abstract: This study aims to ascertain how the capital structure affects firm value via profitability moderated by hedging practices and firm size. Verification analysis is used in this study, with data analysis techniques through conditional process analysis. Companies from miscellaneous industrial sectors that were listed on the Indonesia Stock Exchange between 2016 and 2020 make up the research population. The study showed that: capital structure affects profitability; capital structure and profitability affect firm … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
13
0
3

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 16 publications
(20 citation statements)
references
References 44 publications
4
13
0
3
Order By: Relevance
“…This is because the level of risk attached to the capital structure shall cancel the positive effect of profitability on FV. Moreover, a firm's profitability cannot mitigate the effect of CS on FV (Alghifari [13]). The results of moderating the effect of profitability on firm value with the capital structure are in accordance with the previous research works of Chen and Chen [19] and Alghifari [13].…”
Section: Results Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…This is because the level of risk attached to the capital structure shall cancel the positive effect of profitability on FV. Moreover, a firm's profitability cannot mitigate the effect of CS on FV (Alghifari [13]). The results of moderating the effect of profitability on firm value with the capital structure are in accordance with the previous research works of Chen and Chen [19] and Alghifari [13].…”
Section: Results Discussionmentioning
confidence: 99%
“…Mubyarto [10] and Akhmadi et al [11] studied FV, profitability, and CS in the companies listed on the ISE and found no significant positive association between CS and FV; however, they suggested that profitability can mediate and moderate the relationship between the two. Similarly, a study by Hirdinis [12], Alghifari et al [13] reported a contrasting result where profitability has no mediation effect on CS and FV, while Natsir and Yusbardini [14] reported that profitability could mediate the effect of CS and firm size on FV. Aimomani et al [15] examined the effect of financial leverage on FV by moderating profitability and firm size.…”
Section: Firm Value Moderated By the Profitabilitymentioning
confidence: 95%
See 1 more Smart Citation
“…Previous studies undertaken by Ardini et al (2022), Rahayu et al (2020), and Alghifari et al (2022 have demonstrated a favorable relationship between the capital structure and firm value. This differs from the impact exerted by Doorasamy (2021), Sumani et al (2022, and Hung Ngoc Dang et al (2019).…”
Section: Capital Structurementioning
confidence: 90%
“…According to Alghifari et al (2022), Myers (1977 proposed the trade-off theory. According to this theory, it is posited that the determination of an optimal capital structure is feasible.…”
Section: Capital Structurementioning
confidence: 99%